Stress concentration factors and fatigue behavior of square bird-beak SHS T-joints under out-of-plane bending. (15th September 2015) - Cheng, Bin; Qian, Qin; Zhao, Xiao-Ling
Highlights: We carried out high-cycle fatigue tests for square bird-beak SHS T-joints. We identified critical locations of stress concentrations. We investigated fatigue cracking and failure mode. We compared experimental fatigue data with code S–N curves. Abstract: In this study, fatigue tests of square bird-beak square hollow section (SHS) joints were conducted under out-of-plane bending. Nine orthogonally designed T-joints were fabricated. Static loading was first conducted, during which elastic strain distributions near the potential hot spots were measured. Stress concentration factors (SCFs) at weld toes were calculated using the quadratic extrapolation approach. Critical locations were also identified. Based on the high-cycle fatigue testing that followed, the fatigue crack initiation, propagation and fatigue failure mode were obtained. Variations of the surface crack length and out-of-plane rigidity against number of load cycles were also revealed. The cycle numbers that correspond to through-thickness cracks were observed to be greater than the numbers obtained from S–N curves provided by the IIW code, which indicates that the IIW curves/formulations for conventional joints could also be used to estimate the fatigue lives of square bird-beak joints if the hot spot stress ranges have been properly determined.